Paradox Lost and Paradox Regained: Comments on Chouinard's "The Case for Participatory Evaluation...". (June 2013) - Datta, Lois-ellin
Jill Chouinard, in her article "The Case for Participatory Evaluation in an Era of Accountability" (this issue, p. 237), may be re-iterating what has often been claimed and arguably is infused already in much of our theory and practice: the value of participatory approaches in some, perhaps many situations. She summarizes these claims eloquently and well. Chouinard also may be saying that we should continue to examine evaluation policy in light of a changing world, evolving approaches, and new experiences with a wide range of evaluative thinking. If so, amen, sister. This is an on-going task, but necessary and worthwhile. Less benignly, however, Chouinard may be trying to make the case for participatory evaluation as a new uber-standard for all evaluation, particularly national studies in a "technocratic culture of accountability." If so, I disagree. Such a claim seems unjustified for several reasons, including the benefits and current uses of evaluative multiplism, the limitations of evaluative monotheism, and value of building bridges rather than burning them.